ANALISIS PENGARUH UPAH MINIMUM DAN TINGKAT PENDIDIKAN TERHADAP PENYERAPAN TENAGA KERJA DI PULAU JAWA - Damayanti, Erfani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Java island is the economic center with the largest population in Indonesia. So this causes the inequality that occurs in Indonesia to this day. Dense population growth without being accompanied by maximum labor absorption on the island of Java is the cause of employment problems in Indonesia. Many problems arise, for example poverty, unemployment,This research aims to determine and analyze the influence of minimum wages and education on labor absorption on the island of Java. This research also includes inflation and economic growth as a control variable. The analytical method used is a quantitative method using time series data (2012-2022) and cross section (six provinces on the island of Java) or what is called panel data with the selection of the best model, Random Effect Model (REM) and used regression analysis. This research shows that the minimum wage and level of education has a significant effect on labor absorption on the island of Java.